2014
DOI: 10.1021/la5015708
|View full text |Cite
|
Sign up to set email alerts
|

Successful FCS Experiment in Nonstandard Conditions

Abstract: Fluorescence correlation spectroscopy (FCS) is frequently used to measure the self-diffusion coefficient of fluorescently labeled probes in solutions, complex media, and living cells. In a standard experiment water immersion objectives and window thickness in the range of 0.13-0.19 mm are used. We show that successful FCS measurements can be performed using samples of different refractive index placed in cells having windows of different thickness, even much thicker than nominally allowed. Different water, oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 10 publications
(28 reference statements)
1
29
0
Order By: Relevance
“…To improve the signal/noise ratio of the autocorrelation function, each measurement series was based on 40 scans of the diffusion time, with a duration of 15 s each. More details about the used setup can be found in Banachowicz et al (2014). The results obtained from the experiment were verified by simulation based on a simple bead model, performed in the Hydro++ program (Ortega et al 2007).…”
Section: Methodsmentioning
confidence: 99%
“…To improve the signal/noise ratio of the autocorrelation function, each measurement series was based on 40 scans of the diffusion time, with a duration of 15 s each. More details about the used setup can be found in Banachowicz et al (2014). The results obtained from the experiment were verified by simulation based on a simple bead model, performed in the Hydro++ program (Ortega et al 2007).…”
Section: Methodsmentioning
confidence: 99%
“…When the refractive indexes are different, the correction collar must be adjusted for each measurement separately. 12 Although formally eq 11 used to generate the τ c = f(a c ) curve is a cubic function and the value of a c corresponding to the measured τ c could be calculated analytically using Cardano's formulas, 16 it seems much more rational to solve it graphically by generating the data required to make the plot of τ c = f(a c ) with required accuracy. The same graphical method can be used to obtain the a c value from the c = f(a c ) dependence.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous publications [5,26] we have shown that the spherical aberration due to the diamond window thickness of 1 mm (refractive index n = 2.415) can be compensated by the correction collar of the LWD objective #1. We also demonstrated that this combination of objective #1 and a diamond window can be used for a successful FCS measurement.…”
Section: Fluorescence Correlation Spectroscopy (Fcs)mentioning
confidence: 95%